Factors associated with the use of personal protective equipment (PPE) among firefighters in the Manado Fire Department - Gracia, Benanda; Maddusa, Sri Seprianto; Malonda, Nancy S. H. (E-Jurnal Medika Udayana; Vol 14 No 5 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i5.P08, 2025)
Personal Protective Equipment is very important for firefighters because of their duties that must encounter and deal with hazards. The purpose of this study was to analyze the factors associated with the use of PPE in firefighters at the Manado City Fire Service. This type of research is quantitative with observational analytic research design and using cross sectional study approach. The research was conducted in June - November 2023. The sample in the study was the total population included in the criteria of respondents with a total of 40 firefighters. The results of the analysis using the chi square test with a significance level of ? = 0.05, showed that the factors associated with the use of PPE were the training factor with a p-value of 0.041 (<0.05) and the PPE completeness factor with a p-value of 0.000 (<0.05). Meanwhile, the factors that are not associated with the use of PPE are age factor with p-value 0.477 (> 0.05), tenure factor with p-value 0.317 (> 0.05), education level factor with p-value 0.836 (> 0.05), work accident experience factor with p-value 1.000 (> 0.05). It is hoped that this research will be useful for the Manado Fire Department in establishing policies, planning, and implementing occupational health and safety programs.